PENGARUH KETERAMPILAN (SKILL), ATRIBUT PERSONAL, PENGETAHUAN (KNOWLEDGE), DAN PENGALAMAN AUDITOR DALAM PROSES PELAKSANAAN AUDIT TERHADAP KUALITAS LAPORAN AUDIT YANG DIHASILKAN (Survei pada Kantor Akuntan Publik di DKI Jakarta) - Ridi Halman (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
This study aims to analyze the influence of skills), personal attributes, knowledge, and experience auditors affect the quality of audit reports. The number of final samples obtained that can be included in the test is 158 questionnaires. Scope of the object of research conducted on the auditors who are in several Public Accounting Firm (KAP) in Jakarta. The results showed that the skill of the auditor has a positive effect on the quality of the audit report. The personal auditor attribute positively affects the quality of the audit report. The auditor's knowledge has a positive effect on the quality of the audit report. The auditor's experience has a positive effect on the quality of the audit report.